A Comparative Study of Medical Termination of Pregnancy Act, 1971 with Recent Medical Termination of Pregnancy (Amendment) Bill, 2020 Through Judicial Pronouncement (Medico Legal Update, 2020)
Recently Cabinet has passed the proposed Medical Termination of Pregnancy (Amendment) Bill, 2020. Incurrent bill certain changes has been made regarding the upper limit of gestational age for termination ofpregnancy under MTP Act, 1971. Through this paper researcher will discuss about the drawback of the MTP(Amendment) Bill, 2020 in terms of gestational age with the help of the various judicial pro-announcement.